Live cell screening identifies glycosides as enhancers of cardiomyocyte cell cycle activity - Magadum, Ajit; Renikunta, Harsha V.; Singh, Neha; Estaras, Conchi; Kishore, Raj; Engel, Felix B. (Frontiers in Cardiovascular Medicine, 2022)
Promoting cardiomyocyte proliferation is a promising strategy to regenerate the heart. Yet, so far, it is poorly understood how cardiomyocyte proliferation is regulated, and no factor identified to promote mammalian cardiomyocyte proliferation has been translated into medical practice. Therefore, finding a novel factor will be vital. Here, we established a live cell screening based on mouse embryonic stem cell-derived cardiomyocytes expressing a non-functional human geminin deletion mutant fused to Azami Green (CM7/1-hgem-derived cardiomyocytes). We screened for a subset of compounds of the small molecule library Spectrum Collection and identified 19 potential inducers of stem cell-derived cardiomyocyte proliferation. Furthermore, the pro-proliferative potential of identified candidate compounds was validated in neonatal and adult rat cardiomyocytes as well as human induced pluripotent stem cell-derived cardiomyocytes. 18 of these compounds promoted mitosis and cytokinesis in neonatal rat cardiomyocytes. Among the top four candidates were two cardiac glycosides, peruvoside and convallatoxin, the flavonoid osajin, and the selective α-adrenoceptor antagonist and imidazoline I1 receptor ligand efaroxan hydrochloride. Inhibition of PTEN and GSK-3β enhanced cell cycle re-entry and progression upon stimulation with cardiac glycosides and osajin, while inhibition of IP3 receptors inhibited the cell cycle-promoting effect of cardiac glycosides. Collectively, we established a screening system and identified potential compounds to promote cardiomyocyte proliferation. Our data suggest that modulation of calcium handling and metabolism promotes cardiomyocyte proliferation, and cardiac glycosides might, besides increasing myocardial contraction force, contribute to cardiac repair by inducing cardiomyocyte proliferation.